2015 23rd International Conference on Geoinformatics 2015
DOI: 10.1109/geoinformatics.2015.7378566
|View full text |Cite
|
Sign up to set email alerts
|

Impact of slope, aspect and cloud cover on the distribution of incoming global solar radiation over Pakistan

Abstract: We use a distributed modeling approach to investigate the spatial and quantitative distribution of incoming global solar radiation (GSR) falling over the complex terrain using remote sensing (R S) and geographical information system (GIS). To apply distributed model, we use SRTM digital elevation models (DEM) for impact assessment of slope, aspect orientation and correcting possible sunshine duration over the inclined surface. Similarly, to evaluate the impact of cloud cover on incoming global solar radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Few studies have been found on assessment of solar radiation, specifically radiation components over complex terrain in Pakistan, including Ambreen et al (2011), Sultan et al (2014, and Sultan et al (2015). However, no study has been found on the shortwave radiation estimation in the region (Pakistan) particularly complex terrain and the focus study area.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been found on assessment of solar radiation, specifically radiation components over complex terrain in Pakistan, including Ambreen et al (2011), Sultan et al (2014, and Sultan et al (2015). However, no study has been found on the shortwave radiation estimation in the region (Pakistan) particularly complex terrain and the focus study area.…”
Section: Introductionmentioning
confidence: 99%